Are the first 1,000 days of life a neglected vital period to prevent the impact on maternal and infant morbimortality of infectious diseases in Latin America? Proceedings of a workshop of experts from the Latin American Pediatric Infectious Diseases Society, SLIPE - Debbag, Roberto; Torres, Jaime R.; Falleiros-Arlant, Luiza H.; Avila-Aguero, Maria L.; Brea-del Castillo, Jose; Gentile, Angela; Saez-Llorens, Xavier; Mascarenas, Abiel; Munoz, Flor M.; Torres, Juan P.; Vazquez, Liliana; Safadi, Marco A.; et al. (Frontiers in Pediatrics, 2023)
While the first 1,000 days of life are a critical period in child's development, limited information on the main determinants affecting this period in the Latin America and the Caribbean (LAC) region is available. Therefore, the Latin American Pediatric Infectious Diseases Society (SLIPE) held an ad hoc workshop in May 2022 with an expert panel designed to analyze the main factors impacting the development of childhood in the region during this period and the main causes of maternal infant morbimortality. The aim was to identify priorities, generate recommendations, and advise practical actions to improve this situation. Considerations were made about the challenges involved in bridging the gap that separates the region from more developed countries regarding an optimal early childhood and maternal care. Extensive discussion was conducted to reach consensus recommendations on general strategies intended to reduce maternal and infant mortality associated with infections and immune-preventable diseases during the first 1,000 days of life in LAC.